PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE THINK PAIR SHARE (TPS) UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS V SD NEGERI 011 PEMATANG INDAH KECAMATAN KELAYANG - Suryati, Suryati; Kurniaman, Otang; Witri, Gustimal (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: The purpose of this research is to improve learning outcomes science students of class V elementary school number 011 Pematang Indah District of Kelayang Indragiri Hulu with implement cooperative learning model Think Pair Share (TPS). The subjects were students of class V totaling 14 students, which consists of the top 8 men and 6 women. This study is a Class Action Research (Classroom Actions Research) consisting of 2 cycles. Each cycle carried out with four main activities or phases that plan (planning), action (action) observation (observation) and reflection (Reflection). Based on the results of research and data analysis known that an increase in activity of teachers in the first cycle of the first meeting of 58.33% (Less) later a second meeting to 75% (Enough). At the first meeting of the second cycle increased again to 79.17% (Good) and the second meeting mengjasi increased 83.14% (Good). Similarly, the activity of students in the first cycle of the first meeting of 54.16% (Less) increased at a meeting of the two became 70.83% (Enough). In the second cycle students meeting activity increased again to 83.33% (Good) and the second meeting be 87.50% (Good). In addition to the observations, student learning outcomes also increased the value of the average student base score 62.85, in the first cycle increased to 66.42, while the second cycle into 80.71. Thus it can be said with the implementation of cooperative model Think Pair Share (TPS) can improve learning outcomes science students of class V SDN 011 Pematang Indah District of Kelayang.Keywords : Cooperative Learning Model Student Think Pair Share (TPS), Science Learning Outcomes